Talent scheduling with daily working capacity and scene changeover times - Yang, Zhaoqi; Tanaka, Shunji; Lin, Bertrand M.T. (Omega (Oxford), 2026)
This paper investigates a talent scheduling problem that incorporates daily work capacity constraints and the changeover times between consecutive scenes filmed on the same day. The problem inherently integrates three key optimization challenges: talent scheduling, the traveling salesperson problem, and bin packing. To obtain an optimal solution, we develop two integer linear programming models and a dynamic programming algorithm. Additionally, we introduce a polynomial-time dynamic programming algorithm for the special case where the filming order of all scenes is predetermined. This polynomial-time algorithm is incorporated into a tabu search framework to generate high-quality approximate solutions. Finally, we conduct a computational study to assess the effectiveness and efficiency of all proposed solution approaches. The approach of simplifying the problem structures significantly outperforms other algorithms in solution quality and execution time for large-scale instances. •Formulate talent scheduling with daily working capacity and scene changeover times.•Propose two integer linear programs.•Design two dynamic programming algorithms.•Design a hybrid algorithm with a dynamic program and tabu search.•Conduct a computational study.